PENGARUH PEMBERIAN DOSIS KOMPOS DAN ARANG BAMBU TERHADAP PERTUMBUHAN Neolamarckia cadamba (Roxb.) Bosser PADA LAHAN MARJINAL - Jayani, Faradila Mei; Juniarto, Arief (Fakultas Kehutanan Universitas Lancang Kuning, 2020)
Marginal land is a land that has several limiting factors for a particular purpose so that it takes an effort to increase its productivity. Marginal land intended for planting activities has several limiting factors such as low soil organic matter and low pH. Efforts to increase the productivity of the marginal land can be done with the addition of fertilizer and soil ameliorant. This research aims to analyze combinations of compost and bamboo biochar, having the ability to the optimal increase growth of Neolamarckia cadamba (Roxb.) Bosser in marjinal land. The experimental design used in this research was Completely Randomized Factorial Design with two factors (compost and bamboo biochar). The addition of compost and bamboo biochar increased the height, the diameter, and number of leaves of N. cadamba. The addition of 3 kg compost and 100 g bamboo biochar (K1A1) was the best treatment to increased the height, the diameter, and number of leaves of N. cadamba.